(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses the topical issues of investing in innovative processes, identifies the key factors affecting the innovative activity of tourism enterprises, shows an idea of the additional influence of the state on the innovative activity of enterprises, and draws the appropriate conclusions.